Determining the surface fault-rupture hazard zone for the Pazarcık segment of the East Anatolian fault zone through comprehensive analysis of surface rupture from the February 6, 2023, Earthquake (Mw 7.7) - Softa, Mustafa (Journal of mountain science, 2024)
Following surface rupture observations in populated areas affected by the Kahramanmaraş Earthquake (Mw 7.7) on February 6th, 2023, along the Pazarcık segment of the East Anatolian Fault Zone (EAFZ), this study presents novel insights into physical criteria for delineating surface fault-rupture hazard zones (SRHZs) along ruptured strike-slip faults. To achieve this objective, three trench studies across the surface rupture were conducted on the Pazarcık segment of the EAFZ to collect field data, and earthquake recurrence intervals were interpreted using Bayesian statistics from previously conducted paleoseismological trenchings. The results of the proposed model indicate that the Pazarcık segment produced five significant surface-rupturing earthquakes in the last ∼11 kyr: E1: 11.13 ± 1.74 kyr, E2: 7.62 ± 1.20 kyr, E3: 5.34 ± 1.05 kyr, E4: 1.82 ± 0.93 kyr, and E5: 0.35 ± 0.11 kyr. In addition, the recurrence intervals of destructive earthquakes on the subject in question range from 0.6 kyr to 4.8 kyr. Considering that the last significant earthquake occurred in 1513, the longest time since the most recent surface fault rupturing earthquake on this particular segment was 511 years. These results indicate that, in terms of the theoretical recurrence interval of earthquakes that can create surface ruptures on the Pazarcık segment, the period in which the February 6, 2023, earthquake occurred was within the end of the expected return period. As a result, the potential for a devastating earthquake in the near future is not foreseen on the same fault. Finally, the SRHZ proposed for the Pazarcık section of Gölbaşı village was calculated as a 61-meter-wide offset on the fault lineament to reduce the negativities that may occur in the ruptured area in the future. It is recommended to take into account this width in the settlement of this area and nearby areas.